Social mobility in Ireland in the 1990s: evidence from the 1994 Living in Ireland Survey - Whelan, Christopher T. (Economic & Social Studies, 1999)
In this paper we seek to update findings relating to class mobility outcomes and processes in the Republic of Ireland employing data from the Living in Ireland Survey which was carried out in 1994. We also provide an evaluation of a measured variable model of the mobility process developed on an earlier data set. Our findings confirm that transformation of the class structure has been associated with substantial levels of social mobility. At the same time inequalities of opportunity as reflected in the underlying patterns of social fluidity remain substantial and are constant across cohorts. Gender differences are almost entirely a consequence of occupational segregation and there is no evidence that the underlying processes of class disadvantage operate differently for men and women.
Keywords: Social mobility; Ireland; Survey data